2002
DOI: 10.1111/j.1553-2712.2002.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Ottawa Ankle Rules by Nurses in a Pediatric Emergency Department

Abstract: Trained nurses can accurately apply and interpret the OAR. The incorporation of the OAR into the nursing assessment of children with acute ankle injuries may reduce the number of radiographs ordered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The Ottawa Ankle Rules (OAR) (34)(35)(36) that were developed by Ottawa emergency physicians were adopted to assist in determining if radiography should be used to determine whether radiography would be appropriate to diagnose ankle fracture in a patient experiencing ankle pain. It has been demonstrated that when pediatric emergency department (ED) nurses accurately apply and interpret OAR, children in the hospital ED were treated with a nursing collaborative practice protocol (CPP) to minimize throughput time and expedite patient care (37). This suggests that CPP may be a novel treatment in children with fractured ankles and NMP may be used as a part of CPP.…”
Section: Discussionmentioning
confidence: 99%
“…The Ottawa Ankle Rules (OAR) (34)(35)(36) that were developed by Ottawa emergency physicians were adopted to assist in determining if radiography should be used to determine whether radiography would be appropriate to diagnose ankle fracture in a patient experiencing ankle pain. It has been demonstrated that when pediatric emergency department (ED) nurses accurately apply and interpret OAR, children in the hospital ED were treated with a nursing collaborative practice protocol (CPP) to minimize throughput time and expedite patient care (37). This suggests that CPP may be a novel treatment in children with fractured ankles and NMP may be used as a part of CPP.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Numerous studies have examined nurses' interpretation and application of the OAR. [11][12][13][14] It is clear that the use of the OAR by nurses results in similar diagnostic performance for fracture detection as when the rules are applied by physicians, 15,16 and thus it is believed that emergency nurses can accurately determine which patients require radiographs in the setting of isolated blunt ankle injury. 11,13,16 What remains unclear, however, is whether or not triage nurse initiated ankle radiography shortens ED patients' length of stay (LOS), a factor known to be correlated with patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, some pediatric-specific pathways have been shown to have an effect on ED patient flow. [73][74][75] Developing emergency care pathways that adequately address pediatric issues and prioritize problems in accordance with those of adults is a priority. An increasing number and quality of pediatric-specific triage pathways are available, the most notable being the 5-level triage system.…”
Section: Emergency Care Pathwaysmentioning
confidence: 99%